Pengukuran Kualitas Semen dan Morfologi Spermatozoa Kambing Kacang sebagai Dasar Pembuatan Semen Beku - Nubatonis, Alfred; Wiguna, I Gede Arya; Kolo, Yuliana (Jurnal Ilmu dan Industri Peternakan, 2024)
This research aims to measure the quality of semen and morphology of spermatozoa cells in male goats as a basis for making frozen semen. The increase in the goat population in North Central Timor Regency is still relatively low. The rearing system carried out by the community is still traditional and the goat farming business is used as a side business with livestock ownership ranging from 5-10 heads with 1-2 males. The limited number of male peanut goats greatly limits livestock breeding, so efforts need to be made to groom goat semen in the form of frozen semen. Before freezing semen, it is necessary to know the characteristics of peanut goat semen which are related to the quality of the fresh semen produced as a condition for making frozen semen. Semen collection is carried out 5 times at intervals once a week in the morning using an artificial vagina. The results of macroscopic evaluation of spermatozoa showed that the average volume of semen ejaculated was 0.7 mL ± 0.06; the color is yellowish cream, has a typical smell of peanut goat farming, the consistency is thick, average pH: 6.647 ± 0.11. Meanwhile, microscopically, the mass motility value is: +++ (good), individual motility value: 85% ± 3.07, viability value: 82.5% ± 2.51, concentration: 1.763 x 109/mL ± 0.30 and abnormalities spermatozoa: 11.5 ± 2.16. Results of measurements of spermatozoa cell morphology in male Peanut goats mean head length 7.17 ± 0.65 μm, head width 4.11 ± 0.60 μm, tail length 33.82 ± 3.77 μm and total length of spermatozoa cells 40.99 ± 4 .42 μm . The results of this study can be concluded that male Timor bean goats have high spermatozoa quality and good spermatozoa cell morphometry to be continued in the retail and semen freezing stages.